THE ROLE OF CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE AS A MEDIATING VARIABLE FOR THE INFLUENCE OF GREEN ACCOUNTING ON THE FINANCIAL PERFORMANCE OF PLANTATION COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE 2021-2023 PERIOD - Musa Marolop Lumban Gaol; Mitha Cristina Ginting; Duma Rahel Situmorang; Lamria Sagala (Program Studi Akuntansi Universitas Simalungun, 2025)
This study aims to analyze the effect of Green Accounting on Financial Performance with Corporate Social Responsibility as a mediating variable. The objects of this research are plantation companies listed on the Indonesia Stock Exchange (IDX) for the 2021-2023 period. The approach used in this research is a quantitative method, with secondary data sourced from company annual reports. The research sample consisted of 16 plantation companies listed on the IDX during the 2021- 2023 period, selected using a purposive sampling technique. The data analysis technique applied is path analysis using SPSS 26 software. The results show that Green Accounting has no effect on Financial Performance and Green Accounting is proven to have an effect on Corporate Social Responsibility. In addition, Corporate Social Responsibility has no effect on Financial Performance. The direct relationship between Green Accounting and Financial Performance with a Beta value of 0.229 is greater than the indirect relationship between Green Accounting and Financial Performance mediated by Corporate Social Responsibility with a result of 0.0428. In the resulting mediation, Corporate Social Responsibility is not able to become a mediating variable in the relationship between Green Accounting and Financial Performance